EP1227 Nutritional interventions to improve clinical outcomes in ovarian cancer: a systematic review of randomized controlled trials. (1st November 2019) - Marchetti, C; Mele, MC; Rinninella, E; Cintoni, M; Raoul, P; Scaletta, G; Gasbarrini, A; Scambia, G; Fagotti, A
Abstract : Introduction/Background: Among all gynaecological neoplasms, ovarian cancer has the highest rate of disease-related malnutrition, representing an important risk factor of postoperative mortality and morbidity. Hence, the importance of finding effective nutritional interventions is crucial to improveovarian cancer patient's well-being and survival. Methodology: This systematic review of randomized controlled trials (RCTs) aims at assessing the effects of nutritional interventions on clinical outcomes such as overall survival, progression-free survival, length of hospital stay (LOS), complications following surgery and/or chemotherapy in ovarian cancer patients. Methods: Three electronic bibliographic databases — MEDLINE, Web of Science and Cochrane Central Register of Controlled Trials - were used to conduct a systematic literature search based on fixed inclusion and exclusion criteria, until December 2018. Results: A total of 14 studies were identified. Several early postoperative feeding interventions studies (n=8) were retrieved mainly demonstrating a reduction in LOS and an ameliorated intestinal recovery after surgery. Moreover, innovative nutritional approaches such as chewing gum intervention (n=1), coffee consumption (n=1), ketogenic diet intervention (n=2) or fruit and vegetable juice concentrate supplementation diet (n=1) and short-term fasting (n=1) have been shown as valid and well-tolerated nutritional strategies improving postoperative care. Conclusion despite an acceptable number of prospective trials, there is still a lack of homogeneous and robust endpoints. In particular, there is an urgent need ofRCTs evaluating overall survival and progression-free survival during ovarian oncology treatments. Further high-quality studies are warranted, especially prospective study and large RCTs, with more homogeneous types of intervention and clinical outcomes, including a more specific sampling of ovarian cancer women, to identify appropriate and effective nutritional strategies for this cancer at high risk of malnutrition. Disclosure: Nothing to disclose.